Factors influencing expatriates’ decision to accept international re-assignment in Petronas Carigali Sdn Bhd / Zarina Zaid and Noorwalis Daud - Zaid, Zarina; Daud, Noorwalis (2013)
This research paper is conducted to study the factors that influence expatriates’ decision to accept international re-assignment in PETRONAS Carigali Sdn. Bhd., which is a national oil and gas company and wholly-owned by the government of Malaysia. This research focuses on the expatriates staff’s in PETRONAS Carigali Sdn. Bhd. A theoretical framework then was developed and tested to identify whether expatriates’ decision is influenced by four factors of selection criteria for international assignment which are job related factor, family, cross cultural experiences, personal growth and location. This research is carried out to help PETRONAS Carigali to have a better understanding about expatriates’ motivation to take international re-assignment and therefore helps PETRONAS to reduce the failure to their organization and improve the human resources practices and activities. So, researchers tried to identify the main selection criteria that are important to them. In this research, a total of 150 expatriates in PETRONAS Carigali Sdn. Bhd., has randomly selected as a data sampling. A pilot questionnaire was design and sent to the selected respondents. The purpose is to identify the reliability of the questionnaire. Then, final questionnaires were randomly distributed to respondents through email. Responses then were coded and analysis the finding by using Cronbach’s Alpha, person coefficient correlation and multiple regressions to obtain the findings. The person correlation was used by researchers to see if there are any differences in the means for all variables of interest.